2012
DOI: 10.1002/mnfr.201200006
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens genistein and daidzein affect immunity in the nematode Caenorhabditis elegans via alterations of vitellogenin expression

Abstract: Our studies show that induction of estrogen-responsive vitellogenin(s) by the phytoestrogen daidzein potently increases resistance of C. elegans versus pathogenic bacteria and heat whereas genistein acts in an antiestrogenic manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 46 publications
2
19
1
Order By: Relevance
“…Nuclear hormone receptor family is a key to many important cellular processes, but the role of NHR family in DNA damageinduced programmed cell death remains elusive. Previous study showed that NHR-14/HNF4, which was thought to be an estrogenic hormone receptor [8], was involved in the immune response processes via regulation of vitellogenin expression [22]. In present report, we identified nhr-14/ HNF4 as an important member of NHR in regulation of DNA damage-induced apoptosis.…”
Section: Discussionsupporting
confidence: 49%
“…Nuclear hormone receptor family is a key to many important cellular processes, but the role of NHR family in DNA damageinduced programmed cell death remains elusive. Previous study showed that NHR-14/HNF4, which was thought to be an estrogenic hormone receptor [8], was involved in the immune response processes via regulation of vitellogenin expression [22]. In present report, we identified nhr-14/ HNF4 as an important member of NHR in regulation of DNA damage-induced apoptosis.…”
Section: Discussionsupporting
confidence: 49%
“…C. elegans can be infected by many other bacterial strains (Couillault and Ewbank 2002; Sicard et al 2007; Engelmann et al 2011; Fischer et al 2012, 2013; Julien-Gau et al 2014). Here we showed that P. luminescens TT01 was also highly pathogenic to C. elegans .…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies have indicated that some P. luminescens strains displayed pathogenicity toward C. elegans (Couillault and Ewbank 2002; Sicard et al 2007; Engelmann et al 2011; Fischer et al 2012, 2013; Julien-Gau et al 2014), detailed phenotypes and the roles of host defenses have not been characterized. In this study we tested the pathogenicity of P. luminescens TT01, a mutualistic bacterial strain of the H. bacteriophora TT01 to C. elegans .…”
Section: Introductionmentioning
confidence: 99%
“…Lipid metabolism is an important pathway associated with aging (Nakamura et al, 1999; Gubert et al, 2016). Besides providing energy for developing embryos, VITs are involved in the stress response in diverse organisms (Fischer et al, 2012). VITs were found to act as acute- phase-proteins and to possess bacterial binding and inhibiting activities in different fish-species (Zhang, 2011; Fischer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%